2008
DOI: 10.1542/peds.2007-1487
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Autoregulation in Preterm Infants Identified by Using Spatially Resolved Spectroscopy

Abstract: High coherence between mean arterial blood pressure and tissue-oxygenation index indicates impaired cerebral autoregulation in clinically sick preterm infants and is strongly associated with subsequent mortality. Cross-spectral analysis of mean arterial blood pressure and tissue-oxygenation index has the potential to provide continuous bedside assessment of cerebral autoregulation and to guide therapeutic interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
212
3
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 240 publications
(228 citation statements)
references
References 32 publications
(54 reference statements)
7
212
3
6
Order By: Relevance
“…The majority of abnormal CBF is due to impaired cardiovascular control (38). Abnormal fluctuations in CBF are not usually a problem in term infants because they have the ability to maintain near-constant blood flow in the face of changing perfusion pressures by altering cerebral vascular resistance (autoregulation) (39). However, preterm infants commonly have episodes of impaired autoregulation, primarily due to immaturity of or injury to the cerebral vascular bed (40).…”
Section: Hemodynamic Consequences Of the Initiation Of Positive Pressmentioning
confidence: 99%
“…The majority of abnormal CBF is due to impaired cardiovascular control (38). Abnormal fluctuations in CBF are not usually a problem in term infants because they have the ability to maintain near-constant blood flow in the face of changing perfusion pressures by altering cerebral vascular resistance (autoregulation) (39). However, preterm infants commonly have episodes of impaired autoregulation, primarily due to immaturity of or injury to the cerebral vascular bed (40).…”
Section: Hemodynamic Consequences Of the Initiation Of Positive Pressmentioning
confidence: 99%
“…Tsuji et al found a higher coherence score in the very-lowfrequency range for preterm infants with severe cerebral ultrasound abnormalities (grade 3-4 GMH-IVH or PVL) compared to infants with normal or minimal abnormal ultrasound findings [6]. Also, Wong et al showed highest coherence and gain in the very-low-frequency range (0.003-0.02 Hz) [34].…”
Section: Frequency Ranges For Autoregulation Calculationmentioning
confidence: 99%
“…Clinical factors related to impaired cerebrovascular autoregulation are lower gestational age (GA) [29,34,35], lower birth weight (BW), lower glucose levels [29,34,36], higher clinical risk index for babies (CRIB) score [34], increased infant mortality [34,37], and higher PaCO 2 levels [15,38,39]. Perinatal risk factors such as pregnancy induced hypertension; antepartum hemorrhage and placental infarction are also associated with impaired cerebrovascular autoregulation [29].…”
Section: Clinical Factorsmentioning
confidence: 99%
See 2 more Smart Citations